The Moderating Effect of Dividend Policy on Free Cash Flow and Profitability Towards Firm Value - G.A Sri Oktaryani; Siti Sofiyah Abdul Mannan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
This study is aimed to determine the moderating effect of Dividend Policy on Free Cash Flow and Profitability towards Firm Value. This study use Moderate Regression Analysis (MRA) as tool to analyze the moderating effect of Dividend Policy on the sample tested. Sample are chosen by using purposive sampling method from all manufacture firms that listed on Indonesian Stock Exchange throughout 2010-2015 which offered cash dividend to their shareholders. By using panel data, the findings show that Free Cash Flow and Profitability themselves have significant effect on Firm Value. But conversely, each Free Cash Flow and Profitability does not have significant effect on Firm Value after being moderated by Dividend Policy. It is because the direct effect of Free Cash Flow and Profitability toward Firm value is bigger than the indirect effect. The results indicate that Dividend Policy is just predictor moderation in this case.Dividend Policy, Free Cash Flow, Profitability, Firm Value, Manufacture, MRA